ANALISIS RISIKO KESEHATAN LINGKUNGAN GAS KARBON MONOKSIDA PADA PEDAGANG KAKI LIMA (STUDI KASUS JALAN SETIABUDI SEMARANG) - Eka Wahyuni; Yusniar Hanani Darundiati; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Setiabudi Road is a road with CO concentrations that continue to increase every year. Coupled with the growth of traffic caused the high volume of transportation available on Setiabudi road and affected the concentration of carbon monoxide in the ambient air. The concentration of carbon monoxide in Setiabudi road based on previous research between 15,000 - 21,250 μg/m3. This study aims to analyze the environmental health risks of carbon monoxide gas exposure to the street vendors at Setiabudi road, Semarang City. At some point, the concentration of carbon monoxide gas on Setiabudi Road exceeds the quality standard arranged by the Governor of Central Java’s Decree Number 8 Year 2001. This research used Cross-Sectional research type with Environmental Health Risk Assessment method. The sample of this research was the street vendors and the object samples in this research were the air ambient parameters of carbon monoxide gas. The measurements of carbon monoxide gas were performed at 18 points. The result of this study at 18 points is the concentration of carbon monoxide gas on Setiabudi Road ranges from 2.5 to 12.5 mg/m3 with an average of 5.63 mg/m3. The average exposure time is 10.2 hours, the exposure frequency is 327 days, and the exposure duration is 10.85 years. The conclusion of this study is the analysis of the risk of carbon monoxide exposure in street vendors in Setiabudi road shows the value of RQ value ≤1 for real-time and lifetime exposure which means the risk due to carbon monoxide exposure in realtime and the lifetime still has not shown non carcinogenic health risk.